Re-envisioning Myth in Star Wars: Episode VII: The Force Awakens - Gill, Glen Robert (Journal of religion and popular culture, 2019)
Contrary to some commentaries, Star Wars: Episode VII: The Force Awakens maintains the mythic tenor of the popular film series but does so through a more subtle and nuanced use of mythological archetypes that follows not Joseph Campbell's somewhat basic "hero's journey" model but, rather, the re-creative mode of mythmaking discussed by theorists like Northrop Frye and Claude Lévi-Strauss. Through this method, The Force Awakens cleverly repurposes various classical, Biblical, Celtic, and Arthurian types, reaching deep into the ancient Indo-European tradition in some cases, and reinterprets the Babylonian Epic of Gilgamesh, in particular, so as to present a contemporary feminine/feminist initiation myth.